Media's effect on shaping knowledge, awareness risk perceptions and communication practices of pandemic COVID-19 among pharmacists - Karasneh, Reema (Res Social Adm Pharm, 2021)
Coronavirus disease (COVID-19), an infection of the zoonotic coronavirus, is presenting a healthcare challenge around the globe. This study aims to assess the levels of disease knowledge and risk perception among pharmacists. We also recognize predictors of risk perception and perceived media roles. Methods This is a questionnaire-base cross-sectional study. The questionnaire was developed on a web-based platform and invitations were sent to pharmacists nationwide to participate in the study using social media applications. Results A total of 486 pharmacists participated in this study, where females were dominant (78.6%, n = 382). Most (40.4%, n = 198) pharmacists scored 4 out of 5 in basic disease knowledge, and more than half were able to recognize common methods of spread. Risk was highly perceived among participants, and was predicted by gender, living area, and having children (p < 0,05). Frequency of watching the media and sources of information also influenced both risk perception and perceived media roles. Conclusion Disease awareness among pharmacists, as well as risk perception must be considered for effective risk communication planning. The role of media in shaping perceptions should also be carefully studied to encourage compliance with government containment measures and engagement in preventive behaviors.